Endothelial Cell Activity in Chronic Obstructive Pulmonary Disease Without Severe Pulmonary Hypertension - Cella, Giuseppe; Saetta, Marina; Baraldo, Simonetta; Turato, Graziella; Papi, Alberto; Casoni, Gianluca; Rigno, Manuela (Clinical and applied thrombosis/hemostasis, 2005)
Pulmonary hypertension is common in patients with chronic obstructive pulmonary disease (COPD), but the precise mechanism of vascular impairment in these patients is unknown. We, therefore, decided to investigate whether endothelial cell dysfunction is present in patients with COPD with a wide range of chronic airflow obstruction before the development of severe pulmonary hypertension. Selected plasma markers of endothelial cell activity were studied: nitrate+nitrite (NO-2/NO-3), thrombomodulin (TM), tissue factor pathway inhibitor (TFPI), soluble selectins (endothelium sES, leukocyte sLS, platelet sPS), soluble intercellular adhesion molecule-1 (sICAM-1), and soluble platelet endothelial cell adhesion molecule-1 (sPECAM-1). Twenty-five patients with COPD (forced expiratory volume in one second/vital capacity [FEV1/VC] < 88% predicted) and 29 healthy control subjects were recruited to the study. Among patients nine had a pulmonary artery systolic pressure (PASP) between 15 and 30 mmHg, 13 between 32 and 38 mmHg, 2 had a PASP of 41 and 42 mmHg, respectively. One patient had severe pulmonary hypertension with a PASP of 70 mmHg. The average FEV1 of patients with COPD was 46 ± 4% predicted. As compared to control subjects, patients with COPD showed a significant increase in plasma levels of TM and TFPI, indicating that their endothelial cells are still able to produce potent coagulation inhibitors. Levels of NO-2/NO-3were similar in the two groups of subjects examined, further suggesting preserved endothelial function in patients with COPD. In regard to adhesion molecules, patients with COPD showed a reduction in sLS, sPS, and sPECAM-1, and an increase in sICAM-1. This study shows that endothelial cell activity is largely preserved in patients with COPD without severe pulmonary hypertension, suggesting that these patients, despite quite severe airway obstruction, retain reasonably normal endothelial function until they develop severe pulmonary hypertension.